Excellent short- and long-term outcomes after concomitant aortic valve replacement and coronary artery bypass grafting performed by surgeons in training - Saxena, A.; Dinh, D.; Smith, J.; Reid, Christopher; Shardey, G.; Newcomb, A. (2013)
Objective: No previous studies have specifically addressed the effect of training on outcomes after concomitant aortic valve replacement and coronary artery bypass grafting. This study evaluated the early and late outcomes after concomitant aortic valve replacement and coronary artery bypass grafting performed by surgeons in training. Methods: A retrospective analysis of data collected prospectively by the Australian and New Zealand Society of Cardiac and Thoracic Surgeons Cardiac Surgery Database between June 2001 and December 2009 was performed. Concomitant aortic valve replacement and coronary artery bypass grafting was performed in 2540 patients; of these procedures, 290 (11.4%) were by trainees. Patient demographics, intraoperative characteristics, and early morbidity were compared between trainee and staff cases using chi-square analysis and t tests. Multivariate analyses were used to determine the independent association of training status with 30-day and late mortality. Results: Compared with staff cases, trainee cases were younger (mean age, 73.0 vs 74.2 years; P = .025) and less likely to present with triple vessel disease (27.9% vs 38.3%, P = .001) or previous cardiac surgery (6.3% vs 2.8%, P = .016). Trainee cases had longer mean perfusion (160.4 vs 144.6 minutes, P < .001) and crossclamp (125.2 vs 114.6 minutes, P < .001) times. The incidence of early complications was similar between the 2 groups. On multivariate analysis, trainee status was not associated with an increased risk of 30-day mortality (2.4% vs 4.0%, P = .348). Moreover, there was no significant difference in long-term outcomes, and 5-year survival was comparable in both groups (79.6% vs 77.4%, P = .200). Conclusions: Concomitant aortic valve replacement and coronary artery bypass grafting can be safely and effectively performed by properly supervised trainees in the contemporary era. It is imperative to offer training opportunities to junior surgeons in this complex procedure to ensure quality patient outcomes in the future. Copyright © 2013 by The American Association for Thoracic Surgery.